Contribution of unvegetated tidal flats to coastal carbon flux - Lin, Wei‐Jen; Wu, Jihua; Lin, Hsing‐Juh (Global change biology, 2020)
Unvegetated flats occupy a large area in the intertidal zone. However, compared to vegetated areas, the carbon sequestration of unvegetated tidal flats is rarely quantified, even though these areas are highly threatened by human development and climate change. We determined benthic maximum gross primary production (GPPm), net primary production (NPP) and total respiration (TR) during emersion on seven tidal flats along a latitudinal gradient (from 22.48°N to 40.60°N) in winter and summer from 2012 to 2016 to assess the spatial and temporal variability of carbon dioxide flux. In winter, these processes decreased by 89%–104% towards higher latitudes. In summer, however, no clear trend was detected across the latitudinal gradient. Quadratic relationships between GPPm, NPP and TR and sediment temperature can be described along the latitudinal gradient. These curves showed maximum values of GPPm and NPP when the sediment temperatures reached 28.7 and 26.6°C respectively. TR increased almost linearly from 0 to 45°C. The maximum daily NPP across the latitudinal gradient averaged 0.24 ± 0.28 g C m−2 day−1, which was only 10%–20% of the global average of NPP of vegetated coastal habitats. Multiplying with the global area of unvegetated tidal flats, our results suggest that the contribution of NPP on unvegetated tidal flats to the coastal carbon cycle is small (11.04 ± 13.32 Tg C/year). If the land cover of vegetated habitats is continuously degraded to unvegetated tidal flats, the carbon sequestration capacity in the intertidal zone is expected to reduce by at least 13.10 Tg C/year, equivalent to 1% of global carbon emissions from land‐use change. In winter, benthic production and respiration during emersion on unvegetated tidal flats along the latitudinal gradient decreased by 89%–104% towards higher latitudes. In summer, however, no clear trend was detected across the latitudinal gradient. Quadratic relationships between these processes and sediment temperatures can be described along the latitudinal gradient. The contribution of net primary production (NPP) on unvegetated tidal flats to the coastal carbon cycle is small. If the land cover of vegetated habitats is continuously degraded to unvegetated tidal flats, the NPP in the intertidal zone is expected to reduce by at least 13.10 Tg C/year.